1975
DOI: 10.1007/bf00999939
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchung zur Tagesperiodik verschiedener Kreislauf-und Atemgr��en bei submaximalen und maximalen Leistungen am Fahrradergometer

Abstract: The maximal aerobic power of six highly trained young cyclist, mean age 16.3 years and mean VO2max 4.9 l/min, was directly measured at intervals of 4 hrs. A Latin square design was used for the test order. At submaximal work of O2-consumption 2.4 to 4.4 l/min no circadian variation of any single function was found. However, at maximal work load the differences between the maxima and minima values were 12.4% for maximal work output (W max), 7.8% for expiratory minute volume (V Emax), 5.7% for maximal aerobic po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 3 publications
1
8
0
1
Order By: Relevance
“…The circadian circulatory responses of heart rate at rest and during work obtained in this study confirmed those of earlier studies (3,7,8). In interpreting the heart rate responses, it should be pointed out that the heart rate at night is not low because of less strain but because circadian rhythm exists.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The circadian circulatory responses of heart rate at rest and during work obtained in this study confirmed those of earlier studies (3,7,8). In interpreting the heart rate responses, it should be pointed out that the heart rate at night is not low because of less strain but because circadian rhythm exists.…”
Section: Discussionsupporting
confidence: 91%
“…Although a linear relationship between heart rate and work load can be used for calculations, the V0 2 max will be overestimated at night (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Den Einfluss der Tageszeit auf die Leistungsfähigkeit des Menschen und damit auch von Einsatzkräften belegen zahlreiche Studien aus dem Bereich der Arbeitsphysiologie [18,19]. Dabei schwankt die Leistungsfähigkeit zwischen einem absoluten Minimum gegen 3:00 Uhr nachts [20] und einem Maximum zwischen 16:00 und 18:00 Uhr [21]. Die Verminderung der Leistungsfähigkeit zeigt sich in verlängerten Reaktionszeiten, erhöhten Fehlerraten, einer verringerten Signalerkennungsquote und negativen Auswirkungen auf die Bewältigung kognitiver Aufgaben [18].…”
Section: Allgemeine Lageunclassified
“…Also in respect to maximum oxygen intake, significant higher values occur in the daytime as compared to nighttime. During the morning and early afternoon the oxygen intake increases, reaches maximum values at about 18.00 hours and slowly declines during the evening, reaching minimum levels at night (2,7,8).…”
Section: Rhythmicity In Humansmentioning
confidence: 99%